Aerosol climatology and discrimination of aerosol types retrieved from MODIS, MISR and OMI over Durban (29.88°S, 31.02°E), South Africa. (September 2015) - Kumar, K. Raghavendra; Yin, Yan; Sivakumar, V.; Kang, Na; Yu, Xingna; Diao, Yiwei; Adesina, A. Joseph; Reddy, R.R.
Abstract: The present study represents the characteristics of aerosol optical depth (AOD) retrieved from multiple satellite sensors (MODerate resolution Imaging Spectroradiometer (MODIS), Multi-angle Imaging SpectroRadiometer (MISR), and Ozone Monitoring Instrument (OMI)) during 2003–2013 over an urban–coastal region, Durban (DBN; 29.88°S, 31.02°E, 46 m°asl), situated on the east coast of South Africa. An intercomparison and validation of AOD is performed against the AOD measurements from ground-based AErosol RObotic NETwork (AERONET) Sunphotometer. The results revealed that MISR-AERONET comparison indicated strong correlation compared to MODIS-AERONET comparison. Also, the comparison between MODIS and MISR AODs noticed significant positive correlation over DBN with the overestimation of latter by former. Highest AOD characterizes during the spring (September–November) followed by summer (December–February) and autumn (March–May) with the lowest AOD observed during the winter (June–August) season. The Angstrom exponent (AE470–600 ) indicates predominance of fine-mode aerosols during spring and summer and dominance of coarse-mode aerosols in winter. A HYbrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model is used to locate the origin of airmass transport and understand the variability of aerosol source regions. Finally, the relationship between AOD and AE has been examined to classify different aerosol types and showed seasonal heterogeneity in their contribution depending upon variability in sources. This is the first ever attempt to classify aerosols over this environment. Graphical abstract: Highlights: MODIS and MISR AODs underestimate with validation against AERONET. High AOD noticed during spring due to anthropogenic and transported aerosols. Airmass transport analysis suggests variability in aerosol source regions. First attempt made to classify aerosol types over the study region. Mixed type aerosols dominated the study region during all the seasons.